Effect of habitat and sex on biological indicators and blood biochemistry of Andinoacara rivulatus in the province Los Ríos - Ecuador - Méndez-Martínez, Yuniel; Cevallos-Chevez, Mariuxi F.; Torres-Navarrete, Yenny G.; Cortés-Jacinto, Edilmar; Ramírez-de la Ribera, Jorge L. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The effect of the habitat and sex on biological indicators and blood biochemistry of Andinoacara rivulatus in the province of Los Ríos - Ecuador was evaluated. Were captured 60 specimens for each zone (180 total), the eight of the animals, length, thickness of the head, tail and the factor were evaluated. Blood glucose, cholesterol and triglyceride indicators were determined. A completely randomized design was used with factorial arrangement (three x two), three habitats and two sexes. A double classification analysis of variance was applied considering the habitat and sex as sources of variation. The results showed the highest morphometric values for males and varied with the habitat, except in the body indices, what were the females. The functional relationship between length and weight was established using quadratic regression equations, with greater significance for males with r2 greater than 0.70. No interaction between zones and sex was shown for the blood indicators studied. The results showed interaction between the habitat locations and sex for the different morphometric indicators evaluated. The biochemical indicators of the blood were conditioned by the habitat.